Human induced pluripotent stem cells generated neural cells behaving like brain and spinal cord cells: An insight into the involvement of retinoic acid and sonic hedgehog proteins - Adelaja, Akinlolu Abdulazeez (International Journal of Health Sciences, 2017)
Objectives: The previous studies generated neural progenitor cells (NPCs) from human induced pluripotent stem cells (hiPSCs) using different protocols. However, the nature of the temporal or regional specifi city of NPCs derived using these protocols is not well defined. Therefore, this study aimed to generate age- and region-specific NPCs from hiPSCs, which mimic in vivo fetal brain (FNPC-B) or spinal cord (FNPC-SC) tissues, in the absence or presence of retinoic acid (RA) and sonic hedgehog (SHH). Materials and Methods: Ventral, caudal and posterior neural cells were generated from hiPSCs with morphogens (RA and SHH), or dorsal, rostral, and anterior neural cells by the withdrawal of these morphogens from the NPC-media. NPCs generated from hiPSCs were compared to FNPC-B or FNPC-SC using immunocytochemical staining assays and global microarray for the evaluations of general and region-specific neural cells markers of neural induction, differentiation, and maturation. Microarray profiling results were analyzed using quantitative unpaired t-test (P <0.05). Results: Immunocytochemical analyzes showed that generated NPCs expressed general neural cells markers (PAX6 and MUSASHI-2). Furthermore, FNPC-B and anterior NPCs were characterized with marked expression of cortical neural cells marker (SOX1) when compared to FNPC-SC and posterior NPCs. Microarray profiling results showed the up-regulation of brain cells markers (EMX2 and PAX6) in FNPC-B and anterior NPCs. Similarly, spinal cord cells markers (COL5A2, HOXB5, HOXB7, HOXB8, HOXC4, and HOXD4) were up-regulated in FNPC-SC and posterior NPCs. Conclusion: NPCs that mimic in vivo brain and spinal cord cells can be generated from hiPSCs in the absence or presence of RA and SHH.